Perbandingan Efektivitas Obat Analgetik dan Antiinflamasi Non-Steroid (OAINS) terhadap Penurunan Nyeri dan Inflamasi - Nur Farahdila Fandi; Haryanto Haryanto (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Pain and inflammation are two clinical conditions that often occur together, especially in musculoskeletal disorders. Non-steroidal anti-inflammatory drugs (NSAIDs) are often used because they have dual effects as analgesics and anti-inflammatories. This study aims to compare the effectiveness of several types of NSAIDs in reducing pain intensity and inflammatory responses. This study used an experimental design with test animal subjects divided into several groups, each receiving treatment with different NSAIDs, namely ibuprofen, diclofenac sodium, and mefenamic acid. Pain assessment was carried out using the visual analog scale (VAS) method, while inflammation was measured by observing edema and inflammatory biomarker levels. The results showed that all three types of NSAIDs had a significant effect on reducing pain and inflammation compared to negative controls, but there were differences in effectiveness between drugs. Ibuprofen showed higher potential in relieving pain, while diclofenac was more effective in suppressing the inflammatory process.